Understanding Islam In Indonesia : Politics and Diversity - Pringle, Robert (Editions Didier Millet, 2010)
There are more Muslims in Indonesia than in any other country, but most people outside the region know little about the nation, much less about the practice of Islam among its diverse peoples or the religion’s influence on the politics of the republic. In this illuminating publication, Robert Pringle explains the advent of Islam in Indonesia, its development, and especially its contemporary circumstances. The author’s incisive writing provides the necessary background and demystifies the spectrum of politically active Muslim groups in Indonesia today.